Examining the validity of the Athlete Engagement Questionnaire (AEQ) in a Portuguese sport setting - Paulo Martins; António Rosado; Vítor Ferreira; Rui Biscaia (Universidade Estadual Paulista (UNESP), 2014)
Sport psychology literature suggests that understanding engagement levels is pivotal to promote positive sporting experiences among athletes. The purpose of this study was to examine the psychometric properties of the Athlete Engagement Questionnaire among Portuguese sport athletes. Two distinct samples of Portuguese athletes from different competitive levels were collected, and the results of a confirmatory factor analysis demonstrated a good fit of the model to the data. A review of the psychometric properties indicated that all factors showed good composite reliability, convergent validity, and discriminant validity. In addition, a multi-groups analysis showed the invariance of the model in two independent samples providing evidence of cross validity. Implications of these results for scholars and coaches are discussed and guidelines for future studies are suggested.